Tahlīl Tarjamah Uslūb Al-Kinayah 'Ammā Yustaqbah Zikruh fī Kitāb Al-Nikāh min Al-Qur'ān wa Al-Sunnah - Fauzi, Safran (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2023)
اللغة العربية تتميز بجوانب البلاغة فمنها جانب الكناية والمجاز له دور مهم في تعبير الألفاظ المستقبحة، فلا يمكن أن تعبر تلك الألفاظ المستقبحة بالتصريح المباشر لما فيها من حياء،كما أن رؤية فعله مستقبح لما فيه من حياء كذلك ذكره مستقبح لأن فيه حياء، لذا نحتاخ إلى أن نعرف طريقة صحيحة لتعبير تلك الألفاظ، لأن الألفاظ المستقبحة لها علاق بتعليم الأخلاق الإسلامية وآداب الكلام والمتكلم. كانت هذه الدراسة مبنية على المنهج الوصفي التحليلي، بوصف ألفاظ الكنايات عما يستقبح ذكره في كتاب النكاح الواردة في القرآن الكريم والأحاديث النبوية، ثم بعده بتحليل كل من تلك الألفاظ، فتهدف هذه الدراسة لتعليم الحياء والاحترام بألفاظ مستقبح ذكرها عندالإسلام، وتعليم كيفية الكناية عن الألفاظ المستقبحة، للحفاظ على المروءة من يتلفظ بألفاظ مستقبح ذكرها، ومعرفة أساليب الكناية عن الألفاظ المستقبح ذكره حول كتاب النكاح، ومساعدة متعلمي اللغة العربية على الاهتمام بمروءة نفسه بحيث أنه يحافظ على كلامه خاصة في الألفاظ المستقبح ذكرها باختيار ما يمكن من أحسن الأساليب من الكناية ولكشف أساليب الكناية عما يستقبح ذكره في كتاب النكاح لدى متعلمي اللغة العربية. توصلت هذه الدراسة الوصفية التحليلية إلى أن الألفاظ المستقبحة المستهجنة ذكرها تأتي كلها على سبيل الكناية، خاصة في كتاب النكاح الذي يكثر فيه ألفاظ الاستقباح، إلا في المواضع التي يمكن إدراكها لدى الباحث؛ وقد صرح النبي ﷺ لفظ الجماع في حديثه (( يجامع أهله ثم يكسل )). فتكنى تلك الألفاظ المستقبحة بالألفاظ التي يستحب ذكرها للهدف المهم وهو تنزيه عن الفحش والتفحش المنهي عنه كما أن الإسلام حرص على تطييب الأسلوب والكلام. Arabic has the advantage of balaghoh, among others relating to kinayah and majaz, by its kinayah uslub (method) has an important role in expressing inappropriate words, it is impossible that the words are mentioned explicitly, due to its mention is considered ashamed as to see his deeds, therefore we need the correct way of saying it, because the words are related to the teachings of Islamic ethics as well as the ethics of speech and speaker.This research is based on descriptive and analytical approach, by describing kinayah words about things that are not worth mentioning in marriage chapter contained in Al-Qur'an and hadith, then analyzing each of these words, this research aims to teach modesty and respect in uttering inappropriate words of his mention in Islam, to teach how to kinayah in using such inappropriate words, and to maintain the dignity / self-esteem of the speaker in the pronunciation of these words, to know the method of kinayah words that are not worth mentioning in the chapter of marriage, also helps the Arabic learner in paying attention to his honor especially when speaking with words that are considered inappropriate to his mention so as to be able to choose the methods of kinayah the best method of naming it and revealing the kinayah methods for words deemed inappropriate for his mention in the wedding chapter for Arabic students. This descriptive and analytical study finds that inappropriate words are mentioned in the form of kinayah methods, especially in the Marriage chapter which are often mentioned words that are deemed inappropriate for their mention, except in some known places by the researcher ie, the Prophet ﷺ never uttered the word